A constituição discursiva de instituições bancárias na mídia: Itaú Personnalité e Banco do Brasil - Ferreira, Andréia Nogueira (2009)
The present work presents as theoretical support the studies of the speech accomplished by Pêcheux and mainly by other contemporary authors such as Maingueneau and Charaudeau. We understand that the media world participates in the popular imagination construction, which allows individuals and institutions to realize themselves and to sketch their identities. We took as object of comparative study two series of advertising transmitted in printed media in 2007, such as Piauí, Veja, Isto É, Cláudia, Época, Época Negócios and Você S/A: (a) Advertising from a Banco Itaú’s segment, the Itaú Personnalité, that aims to offer the customers, people with high incomes, a differentiated attendance option, and still, the Itaú Personnalité magazine’s first edition; (b) the most recent Banco do Brasil’s publicity campaign. It intends to analyze the process of those publicity speeches construction, the enunciative scenes and the ethos, observing which are the traces of identity of the referred institutions.